Design, Synthesis and Molecular Docking Studies of Some Tetrahydropyrimidine Derivatives as Possible Fascin Inhibitors. Issue 2 (4th January 2019) - Riahi, Narges; Kefayat, Amirhosein; Ghasemi, Ahmad; Asgarshamsi, Mohammadhosein; Panjehpoor, Mojtaba; Fassihi, Afshin
Abstract: Eight derivatives of tetrahydropyrimidine scaffold were designed and prepared as hybrid compounds possessing the structural features of both monastrol as an anticancer drug and nifedipine as a fascin blocking agent. All of the compounds were evaluated for their cytotoxic potency and the ability to inhibit 4T1 breast cancer cells migration. Then, they were investigated in silico for their ability to inhibit the fascin protein using molecular docking simulation. The most potent compound was4d and the weakest one was4a according to the in vitro cytotoxicity assay. The corresponding IC50 values were 193.70 and 248.75 μm, respectively. The least cytotoxic compound (4a ) was one of the strongest ones in binding to the fascin binding site according to the molecular docking results.4a and4e inhibited the 4T1 cells migration better than other compounds. They were more potent than nifedipine in inhibiting the migration process. In silico studies proved4h to be the most potent fascin inhibitor in terms of Δ G bind although it was not inhibiting migration. The controversy between the in vitro and in silico results may cancel the theory of the involvement of the fascin inhibition in the migration inhibition. However, the considerable antimigratory effects of some of the synthesized compounds encourage performing further in vivo experiments to introduce novel tumor metastasis inhibitors. Abstract :